The impact of cognitive biases on financial decision-making (Economics and region, 2025)
This article examines the problem of the impact of cognitive biases on financial decision-making in the corporate sector. It has been established that cognitive distortions such as overconfidence, loss aversion, anchoring effect, availability heuristic, and status quo bias significantly affect corporate financial strategy. Specifically, overconfidence often leads managers to engage in excessive debt financing, increasing financial risks and the likelihood of default. Loss aversion and the status quo effect contribute to conservative management decisions, thereby limiting strategic growth opportunities for the company. The article analyzes key theoretical approaches to studying cognitive biases in corporate finance, including the behavioral prospect theory developed by D. Kahneman and A. Tversky. The research is based on an econometric analysis of corporate financial decisions, a comparative analysis of corporate strategies, and behavioral experiments in a simulated environment of uncertainty. It has been established that reducing the impact of cognitive biases by 10–20% can increase the share of successful investments by 12–15%, and improve the return on assets and debt-to-equity ratio by 8–10%. The article proposes several practical recommendations for minimizing the impact of cognitive biases in corporate management. In particular, it justifies the importance of implementing scenario analysis to assess risks and forecast financial outcomes, engaging independent experts to provide an objective assessment of financial decisions, and conducting behavioral training for managers to improve risk assessment and decision-making in an environment of uncertainty. An essential tool is the use of group approaches to financial decision-making, which helps balance individual biases and ensure the rationality of financial policy. The research findings can be applied in strategic financial planning and capital management to enhance the effectiveness of corporate financial management.
Keywords: financial decisions; corporate governance; strategic planning; behavioral finance; debt burden; investment activity; dividend policy; mergers and acquisitions (M&A); scenario analysis